2022
DOI: 10.3389/fonc.2022.772102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression disorder on the efficacy and quality of life of first-line chemotherapy combined with immunotherapy in oncogene-driver negative NSCLC patients

Abstract: ObjectiveThe current research was to assess the relevance between depression disorder and first-line chemotherapy combined with immunotherapy, quality of life in patients with oncogene-driver negative non-small cell cancer (NSCLC).MethodsNSCLC patients (33 with depression disorder and 34 with no depression disorder) who was received first-line chemotherapy combined with immunotherapy performed Zung Self-rating Depression Scale (SDS) and European Organisation for Research and Treatment of Cancer Quality of Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Depression has been identified as a prognostic factor for the survival rate of NSCLC ( Andersen et al, 2023 ). Li et al analyzed NSCLC patients with depression and found that the group with depression had a lower PFS compared to the group without depression ( Li et al, 2022b ). There were statistically significant differences in ORR and DCR between the two groups, indicating that depression can affect the efficacy of chemotherapy combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Depression has been identified as a prognostic factor for the survival rate of NSCLC ( Andersen et al, 2023 ). Li et al analyzed NSCLC patients with depression and found that the group with depression had a lower PFS compared to the group without depression ( Li et al, 2022b ). There were statistically significant differences in ORR and DCR between the two groups, indicating that depression can affect the efficacy of chemotherapy combined with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%